2021
DOI: 10.21438/rbgas(2021)082021
|View full text |Cite
|
Sign up to set email alerts
|

BIM plug-in technology for construction waste quantification

Abstract: Current building management standards demand that construction waste management occurs in the planning phase. This paper presents the development of a plug-in as a BIM tool to predict waste generation. As a research strategy, the plug-in was applied to a single-family housing project, the respective construction wastes were predicted in the BIM technology and compared to the literature. Through waste generation indexes, some planning indicators were calculated. The identified wastes were automatically classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Step 1: Quantifying the Types and Quantities of Recyclable CW in BIM Several studies have shown the relationship between the design that covers the construction solutions, materials, and technologies used in buildings and the types and quantities of waste generated [70][71][72]. The types and quantities of waste generated can be ascertained from the building design: manually, using waste quantification models [51,73]; semi-automatically, in various BIM platforms (Allplan 2021.02, Nemetschek AG, Munich, Germany; Archicad 24, Graphisoft, Nemetschek AG, Munich, Germany; Audodesk Revit 21.1.1, Autodesk Inc., San Rafael, California, USA) [22,25,74]; or automatically, such as in BIM (Revit) [23,24,46]. Specifically, certain studies [46,74] integrated the quantification model [51] into BIM, so that automated CDW quantification can be carried out by the designer without effort nor time consumption.…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Step 1: Quantifying the Types and Quantities of Recyclable CW in BIM Several studies have shown the relationship between the design that covers the construction solutions, materials, and technologies used in buildings and the types and quantities of waste generated [70][71][72]. The types and quantities of waste generated can be ascertained from the building design: manually, using waste quantification models [51,73]; semi-automatically, in various BIM platforms (Allplan 2021.02, Nemetschek AG, Munich, Germany; Archicad 24, Graphisoft, Nemetschek AG, Munich, Germany; Audodesk Revit 21.1.1, Autodesk Inc., San Rafael, California, USA) [22,25,74]; or automatically, such as in BIM (Revit) [23,24,46]. Specifically, certain studies [46,74] integrated the quantification model [51] into BIM, so that automated CDW quantification can be carried out by the designer without effort nor time consumption.…”
Section: 21mentioning
confidence: 99%
“…In this vein, Building Information Modelling (BIM) has become a powerful tool for the management of building information [19][20][21] and for the automation of calculations during the design stage [16,21]. In the field of CDW, BIM has been applied with several approaches: (i) to predict CDW generation [22][23][24][25];…”
Section: Introductionmentioning
confidence: 99%